Manipulation on the News Ticker in Telewizja Republika’s News Programs (The phenomena of propaganda and manipulation in the press, radio, television, and internet. Volume III, 2025)
The article analyzes how Telewizja Republika uses on-screen “news banners” (chyrons) in its main newscast “Dzisiaj,” focusing on the role of linguistic persuasion and emotional coloring in short on-screen messages. The study covers the period from May 21 to June 4, 2024, and the corpus consists of 121 banners transcribed and coded both thematically and linguistically. Its aim was to determine whether the banners serve as a neutral complement to the broadcast or—through metaphors, hyperbole, presuppositions, and an “us–them” dichotomy—construct a biased interpretation of reality, including more frequently casting certain actors (e.g., the government) as perpetrators/negative protagonists. A qualitative content analysis was applied, distinguishing the following categories: negative evaluation of the current government, positive/neutral portrayal of the previous administration, emotions, and the overall degree of manipulativeness. The results indicate that 38% of the banners contain clearly evaluative, negatively charged wording; 22% directly demonize the actions of the current government; and only 3% can be read as favorable to the previous ruling team. In total, 42% of the messages contain elements classified as manipulative. The findings suggest the dominance of persuasive over informational strategies and a coherent ideological profile of the coverage, which may reinforce polarization and shape a preferred interpretation of political events.